New car selection in the market using Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method / Mustaqim Ahmad Rosli - Ahmad Rosli, Mustaqim (2020)
Buying vehicle especially cars in the market for now days is hard decision to make due of changes in various technical and operational parameter specification like body shape, design, technology and many more. Therefore, to overcome from this confusion state some selection procedure techniques are required. In the decision-making model, TOPSIS is one of the selection procedure technique to adopted into this research. This technique provides a base for decision making processes where there are limited numbers of choices but each has large number of attributes. In this project some cars are considered with different attributes and ranked car using TOPSIS technique.